2020
DOI: 10.1042/ebc20190091
|View full text |Cite
|
Sign up to set email alerts
|

Role of bioactive sphingolipids in physiology and pathology

Abstract: Sphingolipids are a class of complex lipids containing a backbone of sphingoid bases, namely the organic aliphatic amino alcohol sphingosine (Sph), that are essential constituents of eukaryotic cells. They were first described as major components of cell membrane architecture, but it is now well established that some sphingolipids are bioactive and can regulate key biological functions. These include cell growth and survival, cell differentiation, angiogenesis, autophagy, cell migration, or organogenesis. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 105 publications
1
88
0
1
Order By: Relevance
“…Similar to its effect in many other cell types [15,34], a low concentration of S1P enhanced cell viability in EGFR+ cells (Figure 2B). Since it has been demonstrated that SK1-generated S1P can act through S1P receptors stimulating cell proliferation and survival [19], we investigated the potential correlation between this "inside-out" signaling of S1P and EGFR+ cell survival.…”
Section: Extracellular S1p Is Responsible For the Resistance To Tmz Of Egfr+ Cellssupporting
confidence: 72%
“…Similar to its effect in many other cell types [15,34], a low concentration of S1P enhanced cell viability in EGFR+ cells (Figure 2B). Since it has been demonstrated that SK1-generated S1P can act through S1P receptors stimulating cell proliferation and survival [19], we investigated the potential correlation between this "inside-out" signaling of S1P and EGFR+ cell survival.…”
Section: Extracellular S1p Is Responsible For the Resistance To Tmz Of Egfr+ Cellssupporting
confidence: 72%
“…The biology of sphingolipids has been extensively explored in the peripheral system, and the associated pathologies have also been thoroughly investigated; however, despite being major structural components of the brain anatomy, the functional significance of sphingolipid signaling in the CNS remains underexplored. The majority of published data emphasize the involvement of sphingolipids in inflammatory disorders, such as asthma, chronic pain, rheumatoid arthritis, and infections [ 85 ], and some recent findings indicate their role in neuroinflammation and neurodegeneration as well [ 36 , 86 ]. As mentioned earlier, aspirin is the treatment of choice for inflammatory illnesses, which acts as a nonselective inhibitor of COX2 enzymatic activity and resolves inflammation by abrogating the synthesis of prostanoids.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipids and long-chain unsaturated fatty acids in particular ranked as top predictors of genital inflammation. Emerging studies have demonstrated that sphingolipids are implicated in multiple pathological processes, such as inflammatory diseases, diabetes, and cancer (58). In a previous report we showed that women with cervical cancer had elevated sphingolipids in the cervicovaginal fluids, suggesting that cancer drives associations of phospholipids with inflammation.…”
Section: Discussionmentioning
confidence: 99%